2017
DOI: 10.1016/j.jinorgbio.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of ligand effects in platinum-amyloid-β coordination

Abstract: Ligand field molecular mechanics (LFMM) and semi-empirical Parametric Model 7 (PM7) methods are applied to a series of six Pt-Ligand systems binding to the N-terminal domain of the amyloid-β (Aβ) peptide. Molecular dynamics using a combined LFMM/Assisted Model Building with Energy Refinement (AMBER) approach is used to explore the conformational freedom of the peptide fragment, and identifies favourable platinum binding modes and peptide conformations for each ligand investigated. Platinum coordination is foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…In this sense, one may consider the predominance of the trans ‐912‐T compound in the Tb‐RP solution at room temperature and, thereby, the main contributive conformation to the observed luminescent properties. In the literature, [ 88,89 ] the agreement of relative predominance of metallic complexes conformations is reported calculated by Boltzmann distribution and the experimental data, which may clarify the molecular structure for systems where these data are unavailable, such as the Tb‐RP systems evaluated in this paper.…”
Section: Resultssupporting
confidence: 58%
“…In this sense, one may consider the predominance of the trans ‐912‐T compound in the Tb‐RP solution at room temperature and, thereby, the main contributive conformation to the observed luminescent properties. In the literature, [ 88,89 ] the agreement of relative predominance of metallic complexes conformations is reported calculated by Boltzmann distribution and the experimental data, which may clarify the molecular structure for systems where these data are unavailable, such as the Tb‐RP systems evaluated in this paper.…”
Section: Resultssupporting
confidence: 58%
“…Pt-phenanthroline complexes were bound to the peptide via His6-Nε and His14-Nε, as identified in our previous work. [ 26 ][ 27 ] Initial peptide conformations were selected from a LowMode Molecular Dynamics [ 33 ] simulation in MOE as reported previously. DL_POLY input files were generated using DL_FIELD [ 34 ] and the DommiMOE [ 24 ] extension to MOE.…”
Section: Computational Detailsmentioning
confidence: 99%
“…[ 22 ] Recently, we showed that ligand field molecular mechanics (LFMM) [ 23 ][ 24 ][ 25 ] is an appropriate method to probe the binding of Pt to fragments of Aβ, characterising the effect of Pt complexes on limiting conformational freedom of the peptide [ 26 ] and the role of ligand variation in complexes formed and 3D conformation adopted. [ 27 ] In this work, we extend this approach to examine the dynamical behaviour of a typical Pt-Aβ adduct using molecular dynamics simulations and LFMM description of metal coordination coupled with conventional molecular mechanics (MM) for the peptide.…”
Section: Introductionmentioning
confidence: 99%
“…Here the Ligand Field Stabilization Energy (LFSE) in these complexes is captured in a small number of transferable parameters. LFMM has seen success in modeling a range of Jahn–Teller active Cu­(II) systems, spin states of Ni and Fe complexes and Pt­(II)-biomolecule studies. , Recently, we have shown the suitability of LFMM for description of binding of Cu­(II) and Pt­(II) with fragments of Aβ. …”
Section: Introductionmentioning
confidence: 99%